Pengembangan Bajan Ajar Kritik Sastra dengan Menggunakan Metode Pembelajaran Mandiri - Parapat, Lili Herawati; Lubis, Khatib; Huda, Rahmat (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This development research aims to describe the results of the validation reliability of the development of literary criticism teaching materials using the independent learning method. The problem that often occurs is the lack of textbooks that can support the learning of literary criticism courses, so that students' understanding of theory practice in literary criticism courses is weak. The research method used is the RD development method. The research sample is 4th semester students of the Indonesian Language Education Study Program FKIP UM-Tapsel for the 2021-2022 academic year. Based on the results of development research it is known that the reliability conclusion of developing literary criticism teaching materials using independent learning methods is successful and feasible to be made as literary criticism teaching materials for independent learning.Keywords: Development, teaching materials, literary criticism, independent learning